HUBUNGAN MEKANISME KOPING LANSIA YANG DI TINGGAL PASANGAN DENGAN KUALITAS TIDUR - Hesti Hesti; Darwin Karim; Nopriadi Nopriadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
Losing a life partner is one of the problems faced by the elderly. Efforts to overcome feelings of loss are coping mechanisms that can affect the quality of sleep in the elderly. This study aims to see the relationship between the coping mechanisms of the elderly living in a partner with the quality of sleep in the work area of the Payung Sekaki Health Center. Correlation descriptive research design with cross sectional approach. The sample is 98 respondents, sampling is purposive sampling. The analysis used univariate analysis to see the frequency distribution of respondents' characteristics, description of the coping mechanisms of the elderly living in a partner and description of sleep quality and bivariate analysis using the Chi-square test. The results of this study showed that 64 (65.7%) respondents had maladaptive coping mechanisms and poor sleep quality with p value = 0.374 > (0.05). Based on the results of the study, it can be concluded that there is no relationship between adaptive coping mechanisms in the elderly living with a partner with good sleep quality. The results of this study are expected to be used as a source of information in an effort to improve the health of the elderly, both physically and psychologically. Keywords: Coping mechanism, Elderly, Sleep quality